Crystal structure of di[potassium(diaza-18-crown-6)]dicaesium nonastannide( 4–) diethylenediamine, [K(C12H26N2O4)]2Cs2[Sn9] · 2C2N2H8, a polyanion 2∞[KCs2Sn9]– with low-dimensional arrangement of [Sn9] clusters - Hauptmann R. (Zeitschrift für Kristallographie - New Crystal Structures, 2003)
C28H68Cs2K2N8O8Sn9, monoclinic, P121/c1 (No. 14), a = 13.897(3) Å, b = 16.091(3) Å, c = 26.432(5) Å, β = 91.03(3)°, V = 5909.7 Å3, Z = 4, Rgt(F) = 0.050, wRref(F2) = 0.127, T = 153 K.